Eine Karte der hygrothermischen Klimatypen Afrikas - Lauer, Wilhelm; Frankenberg, Peter (ERDKUNDE, 1981)
The leading concepts are isotherms and isohygromenes. The iso hygromenes are based on potential regional evaporation (pLV). They could be refered to as regional-ecological isohygromenes. The potential regional evaporation (pLV) is based on the product of equivalent temperature and saturation deficit, and varied in accordance with the prevailing spatial conditions by way of a sliding factor of reduction, which contains the soil-plant rate, the transpirational behaviour of the vegetation, the albedo, the oasis effect, the severity and edaphic factors (fig. 1).